Sovereign Wealth Funds in East Asia - World Bank (Washington, DC, 2013)
The massive size, rapid growth, and high-profile investments of Sovereign Wealth Funds (SWFs) in the U.S. and elsewhere in 2007 has attracted the attention of the media, politicians, regulators, and academics over the past year. Some of the SWF investments have been viewed as market stabilizing, for instance the substantial equity investments in large U.S. financial institutions that were recently in financial trouble after the sub-prime mortgage crisis. However, there is great suspicion from many political and academic quarters that SWFs are politically motivated with many SWFs in Asia now at the center of the storm. Although SWFs have been in existence for many decades worldwide, most SWFs in the East Asia and Pacific Region (EAP) are relatively new. The emergence of the SWFs in Asia is largely a by-product of the strong economic development at East Asian countries and the attendant accumulation of foreign exchange reserves, however, there are other types of SWFs in the region. The Governments have taken a concerted strategy to enhance the returns on these excess reserves. The EAP region is an ideal region to take a look at the issues surrounding SWFs since Asia has the full range of funds from long-established funds to brand new funds; from passive portfolio investors to more aggressive strategic investors; from resource-backed funds to foreign reserve-backed funds; and, based in the largest, most highly developed economies to the smallest, poorest economies in Asia. Therefore, the objective of this report is to document the status of Sovereign Wealth Funds in the East Asia Region and to understand the implications of their rapid growth. Many developing countries have recently shifted a higher proportion of their foreign currency earnings from official foreign currency reserves to sovereign wealth funds. Sovereign wealth funds have an estimated $600 billion in assets under management in developing countries, dominated by China ($200 billion held by the Chinese Investment Corporation and $68 billion held by the Central Huijin Investment Company) and Russia ($130 billion held in the Reserve Fund and $33 billion held by the Fund of Future Generations). It should be noted that this amount is small relative to the total level of reserves held by developing countries (estimated at $3.7 trillion at end 2007).